Anemia, iron deficiency, and cobalamin deficiency in cats with chronic gastrointestinal disease. (23rd November 2020) - Hunt, Adam; Jugan, Maria C.
Abstract: Background: Iron deficiency and cobalamin deficiency, as sequelae to chronic gastrointestinal (GI) disease, could result in anemia and increased morbidity in cats with chronic enteropathies. Objective: To evaluate iron deficiency in cats with chronic GI disease and its relationship with hypocobalaminemia, anemia, and disease severity. Animals: Twenty client‐owned cats with primary GI disease. Methods: Prospective, cross‐sectional study. Cats were enrolled at the time of evaluation for chronic GI disease, after exclusion of comorbidities. CBC with reticulocyte indices, iron metabolism (serum iron and ferritin concentrations, total iron binding capacity [TIBC]), serum methylmalonic acid (MMA), cobalamin, and folate concentrations, pancreatic lipase and trypsin‐like immunoreactivity, and disease severity were evaluated. Results: Anemia (hematocrit <30%), iron deficiency, and cobalamin deficiency were diagnosed in 4/20, 7/20, and 8/20 cats, respectively. Hematocrit ( r s = −.45; P < .05) and body condition score ( r s = −.60; P < .01) negatively correlated with MMA. Median TIBC was lower in cats with increased vs normal MMA (218 μg/mL; range, 120‐466 μg/mL vs 288 μg/mL; range, 195‐369 μg/mL; P = .02). Hematocrit ( r s = .51; P = .02), reticulocyte MCV ( r s = .52; P = .02), reticulocyte hemoglobin content ( r s = .71; P < .001), and percent transferrin saturation ( r s = .79; P < .0001) positively correlated with serum iron concentration. Conclusions and Clinical Importance: Functional iron deficiency was common in cats with chronic GI disease. Associations between hypocobalaminemia, iron parameters, and hematologic parameters warrant further investigation on the impact of iron deficiency on chronic GI disease morbidity in cats.